State of Mechanisms of Adaptation to Teaching Loads for High-school Students with Different Levels of Professional Preparedness - G.N. Danilenko; Zh.V. Sotnikova-Meleshkina; O.Ya. Mikhalchuk; K.A. Stepanchenko (Zaslavsky O.Yu., 2013)
Evaluation of functional adaptability of 69 high-school students with different levels of professional preparedness had been carried out. The dynamics of the indices of heart rate variability and hemodynamics indices during the academic year had been studied. The difference in adaptive capacity, depending on the personal characteristics of students, the level of preparedness of adolescents to professional choice had been shown.